2019
DOI: 10.3390/w11112293
|View full text |Cite
|
Sign up to set email alerts
|

Hydrochemical Characteristics, Controlling Factors, and Solute Sources of Streamflow and Groundwater in the Hei River Catchment, China

Abstract: Water scarcity in arid regions is exacerbated by water quality degradation from anthropogenic contamination. In water-scarce regions, it is crucial to identify hydrochemical characteristics and pollution sources for effective water resource management. In this study, the Hei River—located in the Loess Plateau of China, which is an arid region with substantial anthropogenic-induced environmental changes—was selected as the study area to investigate these issues. The major ions of 242 streamflow and groundwater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Obviously, silicate weathering was the major contributor to dissolved solutes in groundwater in the Loess Plateau. This finding was consistent with the results obtained by (Hua et al 2019) and (Kou et al 2019) in studying the source of groundwater solutes in the Loess Plateau. However, compared with other regions, the predominant source of groundwater chemistry was different due to different geological factors and climatic conditions.…”
Section: Quantification Of Source Contributions To Dissolved Solutessupporting
confidence: 93%
“…Obviously, silicate weathering was the major contributor to dissolved solutes in groundwater in the Loess Plateau. This finding was consistent with the results obtained by (Hua et al 2019) and (Kou et al 2019) in studying the source of groundwater solutes in the Loess Plateau. However, compared with other regions, the predominant source of groundwater chemistry was different due to different geological factors and climatic conditions.…”
Section: Quantification Of Source Contributions To Dissolved Solutessupporting
confidence: 93%
“…This EWC increased the river flow in the Ejina Delta, directing two-thirds of the surface runoff to the East River (Supplementary Figure S1) (Zhang J. et al, 2023). Additionally, the inflow from the Hei River is fresh water with a TDS concentration of about 300 mg/L (Kou et al, 2019). Its infiltration promotes groundwater recharge, helping to sustain groundwater resources and restore the groundwater ecosystem (Liu et al, 2022;Zhang J. et al, 2023).…”
Section: Study Areamentioning
confidence: 99%
“…Frontiers in Environmental Science frontiersin.org irrigation (Huang et al, 2020;Hu Y. et al, 2021). Human activities and natural hydrological conditions are the key determinants of groundwater level and quality (Mi et al, 2016;Kou et al, 2019;Wang et al, 2019). Previous studies have indicated that EWC replenishes riparian shallow groundwater (Liu et al, 2022) and improves groundwater quality (Chen et al, 2005;Wang et al, 2019), while agricultural irrigation leads to groundwater depletion and water quality degradation, as well as alters the hydrogeochemical processes of groundwater (Fan et al, 2022;Yan et al, 2023).…”
Section: Human Activities Amplifying Interregional Disparities In Gro...mentioning
confidence: 99%
“…Recent studies have shown that human activities, such as agriculture, urbanization and exogenous acid on rock weathering. Especially in southwest China where karstification is strong, have more and more significant effects on water chemistry and water environment quality ( Chen et al, 2002 ; Ding et al, 2017 ; Kou et al, 2019 ; Lenart-Boroń et al, 2017 ; Li et al, 2016a , 2011a ; Meybeck, 2003 ; Wang et al, 2020 ; Yu et al, 2016 ; Zhang et al, 2017 ; Zhang et al, 2021 ). For example, the exogenetic sulphuric acid and nitric acid generated by human activities accelerate the dissolution of carbonate rocks in the rivers ( Han & Liu, 2004 ; Li & Zhang, 2008 ; Li et al, 2010 , 2011b ; Ma et al, 2023 ), and therefore increases the concentrations of Ca 2+ , Mg 2+ , and HCO 3 − ; The average Cl − /Na + molar ratio of rivers is higher with more urbanized ( Tong et al, 2018 ), and The Cl – , Na + and K + are relatively high in rivers that significantly affected by municipal sewage discharge ( Qin et al, 2018 ); The application of agricultural fertilizer will significantly increase the K + , SO 4 2– , NO 3 – , and Cl – concentrations in the river water ( Etchanchu & Probst, 1988 ), and the SO 4 2– , Cl – , and Na + contents are relatively high in rivers on which industrial and mining wastewater have impacts ( Zhang et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%